Pembuatan Aplikasi Simulasi Training Picking Process Di Warehouse Pt. Schneider Electric Manufacturing Batam - Elisa Margareth Sihombing; Nur Cahyono Kushardianto; Fadli Hamsani; Yogi Ilhami (Politeknik Negeri Batam, 2020)
Warehouse is store to keep the goods production or the result of the production process, which is for a certain period of time will be distributed such as demand. One of the job in this part is as a picker. The location of warehouse is too large and make the picker have little trouble for their job. Simulation game is the way to make this job more attractive and excited. Simulation and training game is one of the games that growing rapidly in various fields include in industry, so this final project will making the game application warehouse picking at PT. Schneider Electric Manufacturing Batam. In this game it can combine with new technologies such as augmented reality technologies or we can call it Augmented Reality(AR). In making this game is using the augmented reality technology in conducting warehouse picking simulation to minimalize the occurrence of errors and harm for the company and train the speed and accuracy of a picker.